THE Relationship Between Cargiver Burden And Mental Health Of Elderly Families At Duren Sawit Dosage Care Surgery, East Jakarta - Zatmiko Hery Prasetyo; Mahyar Suara; Achmad Fauzi (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: The elderly are an age group experiencing declines in physical, psychological, and social function, requiring special attention in terms of health and well-being. Most elderly people in Indonesia are cared for by their own family members. Families play a crucial role as caregivers, providing physical, emotional, and social support to the elderly. Long-term caregiving responsibilities can cause stress and exhaustion in family members, known as caregiver burden. This burden refers to the physical, emotional, social, and economic burden experienced by caregivers while caring for the elderly. This burden can negatively impact the caregiver's mental health, including stress, depression, and anxiety. Research Objective: Knowing the relationship between caregiver burden and the mental health of elderly families. Research Method: This study used a cross-sectional analytical design. The sample in this study was a portion of the elderly family who accompanied the elderly for treatment at the Duren Sawit Regional General Hospital, East Jakarta in November 2025, with a total sample of 60 people. The sampling technique used was asidental sampling. Research Results: The majority of respondents were aged 36-45 years (36.7%), had secondary education (71.7%), and were female (63.3%), had mild mental health disorders (56.7%), and had moderate caregiver burden (60.0%). There was a relationship between caregiver burden and the mental health of elderly family members (p-value 0.001). Conclusions and Recommendations: There is a relationship between caregiver burden and the mental health of elderly family members. It is hoped that families can divide the roles in caring for the elderly so that the burden does not fall solely on one caregiver.